Aggressiveness of care following intracerebral hemorrhage in women and men. (25th July 2017) - Guha, Rahul; Boehme, Amelia; Demel, Stacie L.; Li, Janet J.; Cai, Xuemei; James, Michael L.; Koch, Sebastian; Langefeld, Carl D.; Moomaw, Charles J.; Osborne, Jennifer; Sekar, Padmini; Sheth, Kevin N.; et al.
Abstract : Objective: To compare comorbidities and use of surgery and palliative care between men and women with intracerebral hemorrhage (ICH). Methods: The Ethnic/Racial Variations of Intracerebral Hemorrhage (ERICH) study is a prospective, multicenter, case-control study of ICH risk factors and outcomes. We compared comorbidities, treatments, and use of do-not-resuscitate (DNR) orders in men vs women. Multivariate analysis was used to assess the likelihood of ICH surgery and palliative care after adjustment for variables that were p < 0.1 in univariate analyses and backward elimination to retain those that were significant ( p < 0.05). Results: Women were older on average (65.0 vs 59.9, p < 0.0001), and higher proportions of women had previous stroke (24.1% vs 19.3%, p = 0.002), had dementia (6.1% vs 3.4%, p = 0.0007), lived alone (23.1% vs 18.0%, p = 0.0005), and took anticoagulants (12.8% vs 10.1% p = 0.02), compared with men. Men had higher rates of alcohol and cocaine use. After adjusting for age, hematoma volume, and ICH location, there was no difference in rates of surgical treatment by sex (odds ratio [OR] 0.93 for men vs women, 95% confidence interval [CI] 0.68–1.28, p = 0.67), and there was no difference in DNR/comfort care decisions after adjustment for ICH score, prior stroke, and dementia (OR 0.96, CI 0.77–1.22, p = 0.76). Conclusions: After ICH, women do not receive less aggressive care than men after controlling for the substantial comorbidity differences. Future studies on sex bias should include the presence of comorbidities, prestroke disability, and other factors that may influence management.